1990
DOI: 10.1096/fasebj.4.1.2295381
|View full text |Cite
|
Sign up to set email alerts
|

Altered carbohydrate, lipid, and xenobiotic metabolism by liver from rats flown on Cosmos 1887

Abstract: To determine the possible biochemical effects of prolonged weightlessness on liver function, samples of liver from rats that had flown aboard Cosmos 1887 were analyzed for protein, glycogen, and lipids as well as the activities of a number of key enzymes involved in metabolism of these compounds and xenobiotics. Among the parameters measured, the major differences were elevations in the glycogen content and hydroxymethylglutaryl-CoA (HMG-CoA) reductase activities for the rats flown on Cosmos 1887 and decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…3, 4, 5, 6, 50, 51 Previous reports have shown that microgravity induces hepatic injury and apoptosis. 8, 9 It is well known that hepatocyte proliferation is associated with various types of injuries; however, less is known regarding the connection between liver function injury and hepatocyte cell cycle control under microgravity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, 4, 5, 6, 50, 51 Previous reports have shown that microgravity induces hepatic injury and apoptosis. 8, 9 It is well known that hepatocyte proliferation is associated with various types of injuries; however, less is known regarding the connection between liver function injury and hepatocyte cell cycle control under microgravity.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrates, lipids and enzymes have been reported to be changed under microgravity. 3, 4, 5, 6 Several studies have demonstrated that glycogen, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) of the liver were significantly impacted by spaceflight in humans and rats and by tail suspension (TS) in rats, 7, 8, 9 which suggested that microgravity would lead to liver function derangement. In addition to these alterations of biochemical indexes, simulated microgravity (SMG) induced mild portal endotoxemia, which may contribute to hepatic injury and trigger hepatic apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Abraham et al 128 also studied the activities of 28 different hepatic enzymes in microgravity and observed both increases and decreases in some of these enzymes. The activity of hydroxymethylglutaryl‐CoA (HMG‐CoA) reductase, the rate‐limiting step in the biosynthesis of cholesterol, was also shown to increase in microgravity 129 . In rats flown on Cosmos , the amount of microsomal P‐450 and the activity of aniline hydroxylase and ethylmorphine‐N‐demethylase, cytochrome P‐450‐dependent enzymes, were decreased 129 .…”
Section: Physiological Changes During Space Flightmentioning
confidence: 99%
“…In a study of newts in space, some liver pathology was found in the flight newts, although whether this was directly related to weightlessness was not clear (Yamashita et al 2001). Total cytochrome P450 content and activity were reduced in the livers of rats following 14 d of space flight (Merrill et al 1987;Merrill et al 1990; Rabot et al 2000), and other studies in rats have shown perturbations in liver carbohydrate and lipid metabolism. For example, increased liver triglyceride content (Ahlers et al 1981), changes in fatty acid constitution (Abraham et al 1981), and lower liver cholesterol content (Merrill et al 1987) were found.…”
Section: Introductionmentioning
confidence: 98%